2024
DOI: 10.1186/s12903-024-03896-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of periodontal bone loss patterns and furcation defects from panoramic radiographs using deep learning algorithm: a retrospective study

Sevda Kurt-Bayrakdar,
İbrahim Şevki Bayrakdar,
Muhammet Burak Yavuz
et al.

Abstract: Background This retrospective study aimed to develop a deep learning algorithm for the interpretation of panoramic radiographs and to examine the performance of this algorithm in the detection of periodontal bone losses and bone loss patterns. Methods A total of 1121 panoramic radiographs were used in this study. Bone losses in the maxilla and mandibula (total alveolar bone loss) (n = 2251), interdental bone losses (n = 25303), and furcation defect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
(74 reference statements)
0
0
0
Order By: Relevance
“…In a study by Khan et al, an AI system was developed for assessing bone losses and furcation defects on periapical radiographs, demonstrating successful outcomes [ 27 ]. More recently, Kurt-Bayrakdar et al reported the successful detection of vertical, horizontal, and furcation defects using an AI algorithm developed with U-NET architecture (Albert Ludwig University of Freiburg, Freiburg im Breisgau, Baden-Württemberg, Germany) on 1121 panoramic radiographs [ 28 ]. A study very similar to the current study was conducted by Kurt-Bayrakdar et al in 2020 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Khan et al, an AI system was developed for assessing bone losses and furcation defects on periapical radiographs, demonstrating successful outcomes [ 27 ]. More recently, Kurt-Bayrakdar et al reported the successful detection of vertical, horizontal, and furcation defects using an AI algorithm developed with U-NET architecture (Albert Ludwig University of Freiburg, Freiburg im Breisgau, Baden-Württemberg, Germany) on 1121 panoramic radiographs [ 28 ]. A study very similar to the current study was conducted by Kurt-Bayrakdar et al in 2020 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%